Kuhnian's Paradigmatic Analysis Method As a Solution of Abstract Thinking Difficulties in Social Studies - Mutiani Mutiani; Nana Supriatna; Erlina Wiyanarti; Alfisyah Alfisyah; Ersis Warmansyah Abbas (AL-ISHLAH: Jurnal Pendidikan, 2021)
In general, the intelligence possessed by students is different from one another. The factors influence intrinsic factors, maturity, formation, interests, and freedom. In addition, environmental and educational factors also play a role in the formation of intelligence. This study aims to describe Kuhnian's paradigmatic analysis as a solution to the difficulties of abstract thinking in social studies learning. This study describes the discussion by utilizing a literature study. The research results are described in a paradigmatic analysis. Kuhn thoroughly examines each expert's thoughts and scientific works and reveals his contribution to the scientific revolution. Social studies learning dimensions are explained in the form of social action. Social studies are learning conditions of abstract thinking in the process of causality. The reconstruction to solve the problem of difficulty in abstract thinking in social studies subjects in junior high schools is carried out as follows: 1) Teaching social studies as integrative social studies, 2) implementing social studies learning using a trans-disciplinarity approach, 3) conveying that social studies learning is "advanced knowledge." 4) Applying the inquiry model, and 5) Integrating influential social studies learning.